A New Approach for Symmetry Preserving Partial Eigenstructure Assignment of Undamped Vibrating Systems. (24th June 2015) - Hu, Zhigang; Zhang, Jiafan; Yang, Hongjun; Wang, Guoquan
Abstract : A new approach for the partial eigenvalue and eigenstructure assignment of undamped vibrating systems is developed. This approach deals with the constant output feedback control with the collocated actuator and sensor configuration, and the output matrix is also considered as a design parameter. It only needs those few eigenpairs to be assigned as well as mass and stiffness matrices of the open-loop vibration system and is easy to implement. In addition, this approach preserves symmetry of the systems. Numerical example demonstrates the effectiveness and accuracy of the proposed approach.